The study of the pharmacological activity of thick extract from the leaves of Corylus avellana on the model of peripheral vascular thrombophlebitis in rabbit ear - L. M. Maloshtan; A. S. Kalenichenko (Zaporozhye State Medical University, 2017)
Creation of accessible domestic drug for the treatment and prevention of thrombotic venous damage, which would be able to adjust maximum range of disorders with minimal side effects, is actual direction of the pharmacology. The aim of this work is to study the pharmacological activity of the extract from the leaves of Corylus avellana on the experimental model of thrombophlebitis in rabbit's ears. Materials and methods. Experimental thrombophlebitis was reproduced by overlaying the ligature on the rabbit ear border vein and introduction of Lugol solution in the vein cavity. This model allows to impaired blood flow as a result of stasis and inflammation of the vein wall, which is typical for the majority of thrombotic conditions in humans. Histological studies were carried out in accordance with standardized methods of light microscopy for the more detailed assessment of the pathological process intensity in the wall of the vein and its correction study by medication compared with the control group. Results. It has been established that animals treated with the Corylus avellana leaves extract have damaged area of the ear by 23 % less in comparison with the control group on the first day of the experiment. On the 5th day of the experiment, the extract significantly reduced the inflammation area by 24 %, and on the 10th day - by 73 %. According to expression of the protective effect, the extract statistically significantly prevailed over comparison drug eskuvit throughout all experiment. The study of histological samples showed that the extract contributed to thrombolysis, prevented the destruction of the vascular wall, degenerative changes and reduced inflammation in the surrounding tissues and showed more demonstrative impact compared to the reference drug. Conclusions. The obtained results are an evidence of the anti-inflammatory, vein-protective and thrombolytic action that have the superiority over eskuvit tablets. Thus, the results of this study allow to recommend the extract of Corylus avellana leaves as expressed vein-protective remedy.